Changes in consumer behavior PT. Telkomsel during the COVID-19 pandemic - Effendie, Muhammad Dwi Sakti; Rachmawati, Indira (International Journal Labs, 2023)
The Covid-19 pandemic has significantly impacted consumer behavior in Indonesia, leading to competition between service providers for internet services during work from home policies. Wifi network providers have emerged as an alternative, offering more affordable options, shifting cellular telecommunications shopping activities. This study aims to provide an overview of the transformation of consumer behavior in Malang Raya, focusing on the relationship between consumer knowledge and purchasing decisions. The research used a qualitative method with a phenomenological approach, using purposive sampling techniques. Data collection and data sources use in-depth interview techniques and field observations to produce primary data. Secondary data are obtained using documentation techniques. Results showed that large-scale restrictions by the government affected internet use activities at home, with consumers using more WiFi connections than cellular/mobile connections. The study used case studies, interviews, participatory observation, and secondary data collection to analyze the composition of usage between cellular data and WiFi.